ADMINISTRATIVE REFORMS AND THE EUROZONE CRISIS: A COMPARATIVE STUDY OF GREECE AND PORTUGAL - Lampropoulou, Manto (PEOPLE: International Journal of Social Sciences, 2017)
The Eurozone crisis that erupted in late 2009 had a strong impact on the countries of the EU periphery, triggering a range of fiscal and structural adjustments at all levels of government. Greece and Portugal were most affected by the crisis and embarked on fiscal consolidation programmes in exchange for the external financial assistance packages. Public administration was a key reform area where large-scale adjustments needed to be made in a relatively short period of time. This paper seeks to assess the impact of the fiscal adjustment programmes on the Greek and Portuguese public administrations. Drawing on empirical evidence from the period 2009-2016, the effect of the initiated policies is analyzed with reference to quantitative and qualitative indicators. The findings of the comparative study highlight certain similarities and differences in the way that austerity policies affected the domestic administrative systems. The paper also offers some possible explanations for the observed variations in the outcomes and the prospects of the reform programmes.